2008
DOI: 10.1159/000172618
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Burn: Rinsing and Healing with Ionic Marine Solutions and Vegetable Oils

Abstract: Purpose: We investigated the effects of various rinsing and healing protocols on corneal wound repair and inflammation following alkali burn in rabbits. Methods: We conducted in vitro, in vivo and ex vivo studies. First, different rinse solutions were tested in vitro after incubation of ocular cells with methanol or NaOH. Cell viability was then assessed using the neutral red test (cytofluorometry). Second, NaOH was applied to rabbit corneas and associations of rinse solutions (NaCl 0.9% or controlled ionizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 50 publications
2
5
0
1
Order By: Relevance
“…As it induced cell death as soon as 30 minutes, we also evaluated the benefits of a rinse step after use of this solution and observed that unpreserved saline solutions again avoided cytotoxicity. In each case, the controlled ionization controlled marine solution was more efficient than NaCl 0.9% to rinse contact lenses, which is in accordance with previous results (Dutot et al, 2010;Said et al, 2009). Oligoelements and ions are already known to exert beneficial ocular effects (Dutot et al, 2008b).…”
Section: Efficacy Of a Contact Lens Rinse Step With Unpreserved Solutsupporting
confidence: 92%
“…As it induced cell death as soon as 30 minutes, we also evaluated the benefits of a rinse step after use of this solution and observed that unpreserved saline solutions again avoided cytotoxicity. In each case, the controlled ionization controlled marine solution was more efficient than NaCl 0.9% to rinse contact lenses, which is in accordance with previous results (Dutot et al, 2010;Said et al, 2009). Oligoelements and ions are already known to exert beneficial ocular effects (Dutot et al, 2008b).…”
Section: Efficacy Of a Contact Lens Rinse Step With Unpreserved Solutsupporting
confidence: 92%
“…This cationic marine solution was chosen because of its effectiveness in rinsing chemicals away in a model of ocular burn and in modulating P2X7 cell death receptor activation. 8,9 The rise in the use of MPS has been accompanied by substantially more reports of solution-related complications, in particular corneal staining and inflammatory infiltrates. Most MPS manufacturers recommend rinsing the lenses with the multipurpose solution before insertion of the lens.…”
Section: Discussionmentioning
confidence: 99%
“…The marine solution was chosen according to our previous findings that showed its ability to decrease P2X7 receptor activation (which is induced by MPS) and to rinse ocular cells after chemical burn in a better way than NaCl 0.9%. 8,9 In a previous study, hyaluronic acid showed cytoprotective effects against preservative cytotoxicity. 10 Because active principles in MPS are preservatives, we studied the protective effects of hyaluronic acid against MPS cytotoxicity.…”
mentioning
confidence: 95%
“…This activity, together with the anti-inflammatory effects presented above, may represent primordial factors for the wound contraction and healing process acceleration evidenced in this study. Furthermore, Said and co-authors (Said et al, 2007(Said et al, , , 2009) recently demonstrated that A. moluccana essential oil was capable of conferring ocular cytoprotection, with corneal epithelium regeneration and reduction of inflammatory cell infiltration.…”
Section: Stability Studymentioning
confidence: 99%